2022
DOI: 10.5114/ait.2022.114034
|View full text |Cite
|
Sign up to set email alerts
|

Barotrauma in critically ill COVID-19 patients: a retrospective case-control study

Abstract: Background:There is increased incidence of barotrauma in COVID-19 patients, probably due to disease pathology, oxygen therapy and coughing. We aimed to retrospectively compare the characteristics, associations and outcomes of COVID-19 patients with and without barotrauma in the intensive care unit (ICU).Methods: All adults admitted between October 1st and December 31st 2020 in the ICUs of a COVID-19 hospital were retrospectively analysed for presence of a 'barotrauma event' (presence of at least one of pneumot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
2
7
1
Order By: Relevance
“…Barotrauma was associated with worse outcomes in our study, including a longer duration of IMV, a longer stay in the ICU, and higher mortality. These findings were also observed in other studies [ 18 , 25 ]. Additionally, the rates of ICU and hospital mortality were significantly higher in patients with barotrauma compared with those without barotrauma, and the multivariable regression analysis showed that barotrauma was associated with an almost threefold increased risk of death (OR: 2.784, 95% CI: 1.310–5.918).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Barotrauma was associated with worse outcomes in our study, including a longer duration of IMV, a longer stay in the ICU, and higher mortality. These findings were also observed in other studies [ 18 , 25 ]. Additionally, the rates of ICU and hospital mortality were significantly higher in patients with barotrauma compared with those without barotrauma, and the multivariable regression analysis showed that barotrauma was associated with an almost threefold increased risk of death (OR: 2.784, 95% CI: 1.310–5.918).…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, the rates of ICU and hospital mortality were significantly higher in patients with barotrauma compared with those without barotrauma, and the multivariable regression analysis showed that barotrauma was associated with an almost threefold increased risk of death (OR: 2.784, 95% CI: 1.310–5.918). Higher mortality with barotrauma was also observed in other studies [ 5 , 18 , 25 ]. Whether the increased mortality was solely due to barotrauma or that barotrauma indicated a more severe respiratory illness is not clear.…”
Section: Discussionsupporting
confidence: 85%
“…In a retrospective case-control study by Venkateswaran et al, the authors compared the characteristics, associations, and outcomes of COVID-19 patients admitted to the ICU with and without barotrauma [37]. The number of patients admitted over three months was 827, out of which 30 patients (3.6%) developed barotrauma of various types (pneumothorax was most common, in 26 out of 30 patients).…”
Section: Discussionmentioning
confidence: 99%
“…Dear Editor, We thank the authors of the commentary [1] for their comprehensive analysis of the article [2] and for raising some pertinent points. The authors correctly point out that the flow rate setting is an important factor in the use of a high-flow nasal cannula (HFNC), with low flow rates facilitating patient comfort and ease of use, and higher flow rates being more effective at improving oxygenation [3].…”
Section: Letters To the Editormentioning
confidence: 99%